Trends in Project-Based Learning Implementation in Science Education (2015-2025): A Systematic Literature Review - Kharisma Sulistya Akhmadi; Heru Kuswanto; Sul Daeng Naba (Berkala Ilmiah Pendidikan Fisika, 2026)
The paramount goal of this study was to meticulously identify and critically analyze contemporary trends regarding the integration of the Project-Based Learning (PjBL) pedagogical model within science education settings. The adopted research strategy was a Systematic Literature Review (SLR), strictly adhering to the PRISMA framework guidelines, with rigorously defined inclusion and exclusion criteria. The literature sources for this review were exclusively focused on national journals indexed in the Science and Technology Index (SINTA), specifically tiers SINTA 2, SINTA 3, and SINTA 4. The search utilized core keywords encompassing the "PjBL learning model" in the context of physics and science. A comprehensive synthesis of 82 published Indonesian articles revealed key findings: The most frequently investigated learning outcome variable in PjBL implementations was creative thinking skills, cited in the largest proportion of studies at 25%, closely followed by critical thinking skills (17%). However, this review identifies a significant research gap: existing studies are heavily centralized at the Senior High School (SMA) level and rely predominantly on quantitative methodologies, leaving a deficiency in the deep exploration of student learning processes and affective-psychomotor impacts across diverse educational levels. Practically, these findings serve as a strategic roadmap for educators to diversify PjBL application beyond common topics like Fluids and Work-Energy, while providing a robust empirical foundation for developing more holistic 21st-century skill assessments in science classrooms. Methodologically, the quantitative research design featuring the Quasi-Experimental model emerged as the predominant approach, evidenced in 27 articles. In terms of temporal distribution, the highest volume of publications occurred in 2024, contributing 25 articles to the dataset. Furthermore, the content areas most frequently investigated were Static and Dynamic Fluids, covered in 9 articles, and the topic of Work and Energy, featuring in 7 published articles. The insights generated from this research are expected to offer a valuable and significant contribution to the educational sector, particularly in guiding the evaluation and subsequent enhancement of science instruction facilitated by the PjBL model.